2017
DOI: 10.1007/s10157-017-1512-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient knowledge and adherence to maintenance hemodialysis: an International comparison study

Abstract: Age-adjusted HD knowledge was higher and non-adherence rates were lower in Japan vs. the US. However, because of the unexpected finding of 100% adherence in Japan, we were unable to formally test whether knowledge was significantly associated with adherence across both countries. Further research is needed to understand the reasons behind the higher non-adherence rates in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
9
0
5
Order By: Relevance
“…Knowledge scores were not satisfactory at baseline (below the 60% cutoff used) and increased significantly to reach a mean score of 68.1%. It seems that the association between knowledge and dietary nonadherence in dialysis patients is not always clear [ 39 ]. In the results of this prospective pilot, nonadherence to the phosphorus content of the diet increased after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge scores were not satisfactory at baseline (below the 60% cutoff used) and increased significantly to reach a mean score of 68.1%. It seems that the association between knowledge and dietary nonadherence in dialysis patients is not always clear [ 39 ]. In the results of this prospective pilot, nonadherence to the phosphorus content of the diet increased after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients knowing their target weight is similar to ndings in US patients 28 and the differences between units re ect international differences. 29 Younger age and higher education have also previously been linked to patients' knowledge of haemodialysis. 30 However, unlike our results, a study of Norwegian patients suggested some patients feel their input into decisions around uid removal on HD is not considered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the rates of non-adherence to oral medications in chronic hemodialysis patients ranged from 3 to 80% (Schmid et al, 2009 ) and that approximately half of hemodialysis patients are non-adherent to medication therapy (Neri et al, 2011 ). However, non-adherence rates have been reported to be lower in Japan than in the U.S. (Miyata et al, 2017 ). The same was found in the present study.…”
Section: Discussionmentioning
confidence: 99%